Interactive Processes in Grief and Couples' Adjustment After the Death of a Child. (April 2019) - Albuquerque, Sara; Ferreira, Luana Cunha; Narciso, Isabel; Pereira, Marco
The death of a child is an individual process of grief but also a context of significant relational processes, which have been only rarely considered in research. The aim of this study was to examine the interactive processes within bereaved parents. Eighteen married bereaved parents were interviewed individually. The semistructured script included questions about the couples' relationship after the death of the child, particularly the relational dynamics and the association between the individual and relational realms. Data analysis using constructivist grounded theory allowed for the development of a circular hypothesis, suggesting that parents' individual grief influences and is influenced by the couple's relationship and partner support, involving interdependence and patterns of emotional transmission (empathy and emotion contagion) within the couple. The findings suggested that psychological interventions should include the dyadic level to optimize mutual support and the benefits obtained within marital interactions.